Learning Islamic Education in Elementary Schools - Zulhijra Zulhijra; Stephanie Putri Anggraini; Dewy Agustin; Devy Agustin (Universitas Muhammadiyah Enrekang, 2024)
This article explains the reasons for Islamic religious education in elementary schools. Elementary school-age children's thinking abilities develop gradually. To achieve success in educational goals, they must be understood wisely. Descriptive qualitative methods were used in this research. In other words, descriptive analysis is used to collect, organize, and interpret data. The research results show that Islamic religious education in elementary schools differs greatly. If children think imaginatively at first, they become more rational and objective. The study of Islamic religion includes the Koran, creed, morals, fiqh or worship, and the history of Islamic culture. The educational methods that can be applied are Qur'anic education methods, including the install, qishah, ibrah mauidzah, hiwar jadali, uswah hasanah, and targhib tarhib methods. Islamic religious education, on the other hand, can be provided verbally or non-verbally, written or written, and is intended to measure intellectual, social, and spiritual competence. Therefore, it is hoped that Islamic religious education will produce individuals who continue to improve their faith, piety, and morals while actively building Islamic civilization daily.